Impact of the COVID-19 Pandemic on Medical Oncology Workload: A Provincial Review. - Sheridan, Margaret; Colwell, Bruce; Lamond, Nathan W. D.; Macfarlane, Robyn; Rayson, Daniel; Snow, Stephanie; Wood, Lori A.; Ramjeesingh, Ravi (Current Oncology, 2023)
(1) Background: Cancer is the leading cause of death in Canada, with significant resource limitation impacting the delivery of cancer care nationwide. The onset of the COVID-19 pandemic forced additional resource restriction and diversion, further impacting care delivery. Our intention is to analyze the impact COVID-19 on a provincial medical oncology workload and bring attention to the limitations of the current workload metric for oncologists. (2) Methods: All medical oncology patient encounters were extracted and compared, collected by year and encounter type, from April 2014 through March 2022. (3) Results: There was an increase in all patient encounters by an average of 9.5% per year, including during the strictest COVID-19 restrictions. There was an increase in virtual care encounters from 37.9% to 52.1%. (4) Conclusions: Medical Oncology workloads have increased over time and estimates suggest growing demand. Little data exist to inform workforce requirements and actual workload is not captured by the current metric. Though volume of new consults continues to increase, COVID-19 has highlighted additional changes in the delivery of care, likely with lasting impact, little of which are included in the current workload metric.